(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Background: Cemento-osseous dysplasia (COD) is the most common benign fibro-osseous lesion of the jaw, predominantly affecting women in the fourth to sixth decades of life. Despite being a well-recognized entity radiologically and histologically, the genetic mechanisms underpinning COD are poorly understood. Recent advances in genomic sequencing have identified somatic mutations in components of the RAS-MAPK signaling pathway and the TGF-β receptor family, notably KRAS and TGFBR2. These discoveries raise important questions regarding the biological basis of COD and its distinction from other fibro-osseous lesions such as cemento-ossifying fibroma. Objective: This systematic review aimed to evaluate and synthesize current evidence on the involvement of TGFBR2 and KRAS in COD, with emphasis on molecular pathogenesis, diagnostic implications, and potential clinical relevance. Methods: A systematic literature search was performed in PubMed, Scopus, Embase, and Google Scholar up to August 2025. The study followed PRISMA 2020 guidelines, and the protocol was registered in PROSPERO (CRD420251140937). Eligible studies included original research, case series, or case reports describing TGFBR2 and/or KRAS alterations in COD. Data extraction focused on study design, genetic variants identified, allelic frequency, and conclusions drawn by the authors. Results: Out of 127 records screened, five studies met the inclusion criteria. Owosho et al. (2025) reported TGFBR2 hotspot variants (p.Arg528His, p.Arg553His) and noncanonical KRAS mutations (splice variant and p.Lys167Arg) in COD, although at low allelic frequencies. Haefliger et al. (2023) provided broader evidence that RAS-MAPK pathway activation is a recurrent mechanism in COD, implicating KRAS alongside BRAF, HRAS, and FGFR3. Breimer et al. (2025) identified a novel NOTCH4 splice mutation, highlighting molecular heterogeneity. Large clinicopathological analyses by Gomes (2024) and Decolibus (2023) emphasized diagnostic overlap between COD and cemento-ossifying fibroma and advocated for molecular profiling to refine classification. Conclusions: Current evidence suggests that TGFBR2 and KRAS alterations contribute to COD pathogenesis, likely through dysregulation of RAS-MAPK and TGF-β signaling. These mutations, however, are subclonal and infrequent, implying that additional genetic drivers remain unidentified. Incorporating molecular profiling into diagnostic practice could aid in differentiating COD from other fibro-osseous lesions. Larger, multi-institutional sequencing studies are warranted to validate these findings and explore therapeutic relevance.